Radiosynthesis of 11‐[18F]fluoroundecyltriphenylphosphonium (MitoF) as a potential mitochondria‐specific positron emission tomography radiotracer1. (10th September 2013) - Li, L.; Brichard, L.; Larsen, L.; Menon, D. K.; Smith, R. A. J.; Murphy, M. P.; Aigbirhio, F. I.
<x xml:space="preserve">Abstract</x> Changes in the magnitude of the mitochondrial membrane potential occur in a range of important pathologies. To assess changes in membrane potential in patients, we set out to develop an improved mitochondria‐targeted positron emission tomography probe comprising a lipophilic triphenylphosphonium cation attached to a fluorine‐18 radionuclide via an 11‐carbon alkyl chain, which is well‐established to effectively transport to and localise within mitochondria. Here, we describe the radiosynthesis of this probe, 11‐[18F]fluoroundecyl‐triphenylphosphonium (MitoF), from no‐carrier‐added [18F]fluoride and a fully automated synthetic protocol to prepare it in good radiochemical yields (2–3 GBq at end‐of‐synthesis) and radiochemical purity (97–99%). Copyright © 2013 John Wiley & Sons, Ltd.